Dampak Otonomi Khusus dan Pemekaran Daerah terhadap Perencanaan Pembangunan Ekonomi Regional di Papua - Alfani Laura Harikedua (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the impact of special autonomy and the establishment of new autonomous regions (DOB) on regional economic development planning in Papua through a systematic literature review approach. Special autonomy has provided significant fiscal support for local development, while regional expansion aims to improve public service delivery and accelerate progress in underdeveloped areas. The findings reveal that despite increased budget allocations, development outcomes remain constrained by weak governance, limited institutional capacity, and suboptimal community participation. The creation of DOB has added layers of complexity to development planning due to fiscal fragmentation, administrative burdens, and coordination challenges between regions. This study highlights the need for stronger interregional coordination, financial governance reforms, and enhanced involvement of indigenous communities in planning processes. The implications underscore that the success of decentralization policies depends not only on resource distribution but also on institutional quality and synergy across government levels. Furthermore, this study identifies research gaps regarding the long-term effects of DOB policies and calls for empirical studies to enrich the understanding and effectiveness of economic development planning in Papua.